Survey Sarana dan Prasarana di Padepokan Pencak Silat Kota Salatiga pada Tahun 2022 - Tamam Saifurrahman, Muhammad Choirul; Nurharsono, Tri (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the feasibility and suitability of training facilities and infrastructure in hermitages in Salatiga City. The method in this research is qualitative. The location of this research was conducted in the vicinity of Salatiga City, Central Java Province. The object of this research is the existing facilities and infrastructure in each Penccak Silat Padepokan in Salatiga City. Data collection methods are divided into two, namely interview and documentation methods. The data analysis technique used in this research is to use data collection, data reduction, data display, verification and confirmation of conclusions. The results of the research on the feasibility of facilities and infrastructure according to the 2012 IPSI MUNAS in Salatiga City were in the proper category with good conditions. From the five universities studied by the researchers, there were four hermitages that practiced using IPSI mats regularly and were equipped with competitive clothing, match equipment in match numbers, single arts. , doubles and teams as well as good training support infrastructure and in accordance with the 2012 IPSI MUNAS. The suitability of training support facilities in each hermitage in the city of Salatiga is in poor condition, because there are only two hermitages that facilitate good training support facilities and infrastructure.